A Systematic Process for Computing Bourdieusian Social Capital within Institutional Profiles on Twitter - Ferreira, Guilherme Augusto da Silva; Gomes, Alan Keller (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2021: Proceedings of the 27th Brazilian Symposium on Multimedia and the Web, 2021)
This work presents a systematic process for computing Bourdieusian Social Capital (BSC) within institutional Twitter profiles. Based on the observation of sociability practices (social interactions) with the support of Pierre Bourdieu's Theory, we capture data related to these practices, crystallized through performing actions such as Tweet, Comment, Retweet and Like. Next, social interactions are extracted from the captured data as sequences of actions and they are used to compute the effective mobilization capacity of each profile. Finally, the BSC volume is measured by using the effective mobilization capacity, the number of social interactions and the number of followers. The results obtained are aligned with the Bourdieu theory and the systematic process allows to compute the continuous sociability effort of each profile to maintain and expand its BSC. Moreover, the results show that polarities positive and neutral impacts in the composition of the BSC volume.